ROAD SAFETY INVESTIGATION IN CIPULARANG TOLL ROAD - Nabila, Syahla
Traffic safety is an important issue in the field of transportation. Toll roads are one of the infrastructures that are prone to accidents because on toll roads drivers can drive their vehicles at high speeds so there is a high risk of having an accident, as happens every year on the Cipularang Toll Road. This study reviews the safety of the Cipularang Toll Road by knowing the characteristics of accidents that occur on the toll road, identifying segments that need priority treatment, and providing recommendations for appropriate treatment for the five segments with the highest priority for handling. Accident data and traffic data for the last five years (2018-2022) were obtained from PT Jasa Marga Purbaleunyi. Identification of accident-prone segments is carried out using ten performance indicators contained in HSM (2010), namely average accident frequency, accident rate, critical level, Equivalent Property Damage Only (EPDO) average accident frequency, relative severity index, excess prediction of the average accident frequency using the moment method, Level of Service of Safety (LOSS), the excess of the average accident frequency prediction using SPF, the probability of a certain type of accident exceeding the threshold proportion, and the expected average accident frequency with Empirical Bayes adjustments ( EB). Then five segments with the highest priority were selected for treatment and recommendations for appropriate treatment were selected based on the characteristics of the accidents that occurred and the geometric deficiencies and the road environment in these segments and a cost-benefit analysis. The results of the analysis show that the five segments with the highest priority for treatment are KM 91-92 Line B, KM 92-93 Line B, KM 120-121 Line A, KM 101-102 Line A, and KM 86-87 Line B. There are several problems with road conditions and road equipment in these segments so that recommendations for appropriate handling are given such as adding signs and markings, safety fences on the side of the road, and street lighting.